Entrepreneurial communities and family enterprises of India: An overview of their emergence and sustained growth. Issue 1 (12th March 2018) - Bakhru, Kanupriya Misra; Behera, Manas; Sharma, Alka
Abstract : Purpose: This paper aims to examine the traditional business communities and family businesses of India, their emergence and sustained growth. Design/methodology/approach: The authors analyze the role of business communities in family businesses of India and identify business communities that have still sustained and marked a global presence. Findings: Business communities such as Marwaris have the knack for business activities and are leaders of family businesses in India today, who have sustained their past success and continue to create new histories. Other traditional business communities such as Parsis, Sindhis, Chettiars and Gujarati banias have not been able to sustain much. Possible reasons were switching to white-collar jobs, taking up diplomacy and other professions, inter caste marriages, international migration in search of business and Indian government policies. Research limitations/implications: This study provides a useful source of information for academics, policy-makers and economists. Practical implications: Traditional business communities populate the list of family businesses that have marked their global presence. This paper identifies various factors that are responsible for the growth and sustainability of these business communities. Social implications: The study clarifies the role of business communities in domestic economic development. Originality/value: The paper explored traditional business communities of India and assessed their role in family businesses of India that currently mark a global presence.